Rational Utilization of Sediment Resources Improves Rice Yield and Nitrogen Use Efficiency under Salt Stress - Shenghai Cheng; Aibin He; Xiayu Guo; Rongyi Li; Jianbo Wang; Yucheng Qi; Pengfei Zhang; Weixu Tao; Junchao Ji; Tingcheng Zhao; Yusheng Li; Zhiyong Ai (Agriculture, 2024)
Soil salinization negatively affects rice growth and yield; however, how different sludge sources regulate rice growth and yield under salt stress was rarely investigated. This study evaluated the performance of two salt-tolerant rice cultivars, Chaoyou 1000 and Longliangyou 506, grown in two sediment sources, pond sediment (PS) and river sludge (RS), under salt stress (56 ds m−1 brine irrigation) with conventional soil (CS) used as the control. The results showed that the rice yield under the PS and RS treatments was enhanced by 51.0% and 43.6% as compared with CS, respectively, owing to an improvement in spikelet per panicle, 1000-grain weight, dry matter accumulation, and the chlorophyll content in both rice cultivars. Compared with CS, the total nitrogen accumulation, nitrogen grain production efficiency, nitrogen harvest index, and nitrogen partial productivity under the PS and RS treatments were increased by 18.9–28.9%, 17.0–20.6%, 7.2–16.6%, and 43.8–50.9%, respectively. Moreover, rice grown in PS and RS showed higher activities of nitrogen metabolism-related enzymes (nitrate reductase, glutamine synthetase, and glutamate synthetase) at the heading stage and higher K+ and K+/Na+ contents in the leaves. Overall, a balanced utilization of sediment resources (especially pond sediment) can effectively alleviate salt stress and improve the yield and nitrogen use efficiency in rice.